MANAGING FINANCIAL STABILITY BY THE EUROPEAN CENTRAL BANK IN THE PERIOD 2008–2012 - Ciukaj, Radosław (Copernican Journal of Finance & Accounting, 2017)
In reaction to the global financial crisis and ineffectiveness of traditional monetary policy, European Central Bank undertook a number of unconventional measures to preserve financial stability in the EU. The paper presents a non-standard tools used by the ECB in the 2008–2012 period, as a response to shocks in the financial system and evaluates their effectiveness.